2006
DOI: 10.1111/j.1526-4610.2006.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Prevalence in Adolescents Aged 12 to 17: A Student‐Based Epidemiological Study in Bursa

Abstract: Age and gender appeared to be demographic factors increasing adolescent headache prevalence. Frequent episodic-tension type headache was the most common headache followed by migraine. Our migraine prevalence was slightly higher than most of the previously reported prevalence rates. This might be due to the new classification criteria of headache released by International Headache Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 22 publications
9
37
1
2
Order By: Relevance
“…In the age group from 12 to 18 years of age, children presenting more frequent headaches were prevalent. These results are in accordance with that of other population-based studies showing increased prevalence of headaches with advancing age 1,9,11 . Our study gives rise to some questions regarding methodological aspects.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the age group from 12 to 18 years of age, children presenting more frequent headaches were prevalent. These results are in accordance with that of other population-based studies showing increased prevalence of headaches with advancing age 1,9,11 . Our study gives rise to some questions regarding methodological aspects.…”
Section: Discussionsupporting
confidence: 93%
“…A few studies found higher prevalence rates: 92% in Dutch children and adolescents (from 10 to 17 years) 8 and 83% in the Brazilian study 12 . A Turkish study showed a prevalence rate of 53.2% in adolescents ranging from 12 to 17 years of age 11 , lower than that found in our sample.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The association of headaches with age is found by other authors such as Lateef et al [19], Rho et al [20] or Karli et al [21] who show a prevalence of headaches increasing with age. This result may be due to the immaturity of young people who have difficulty describing their symptom and the number of activities whose rate increases with age.…”
Section: Discussionsupporting
confidence: 55%
“…3 La mayoría de las cefaleas en los niños se debe especialmente a situaciones como las cefaleas primarias. La etiología de la cefalea en los niños y adolescentes puede determinarse principalmente con base en el registro detallado de los antecedentes y en un examen n e u r o l ó g i c o i n t e g r a l .…”
Section: Introductionunclassified